2013
DOI: 10.1074/jbc.m113.486852
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor γ (PPARγ) and Its Target Genes Are Downstream Effectors of FoxO1 Protein in Islet β-Cells

Abstract: Background:The molecular mechanisms for islet ␤-cell compensation and failure are not fully known. Results: FoxO1/PPAR␥ signaling regulates key ␤-cell genes, with this network being up-regulated in nondiabetic insulinresistant rats and impaired in rodents with diabetes. Conclusion: We examine the potential for the FoxO1/PPAR␥ network as a feature of ␤-cell compensation and failure. Significance: We identify targets for prevention of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…Rosen et al showed that loss of PPARγ in pancreatic β-cells was associated with a hyperplastic response, but no metabolic abnormalities [38]. More recently, a FoxO1/PPARγ mediated network was proposed as a core element for β-cell compensation and failure in response to metabolic stress [39]. Overall our study shows that lack of PPARγ does not lead to defects in pancreatic beta cell function.…”
Section: Discussionsupporting
confidence: 61%
“…Rosen et al showed that loss of PPARγ in pancreatic β-cells was associated with a hyperplastic response, but no metabolic abnormalities [38]. More recently, a FoxO1/PPARγ mediated network was proposed as a core element for β-cell compensation and failure in response to metabolic stress [39]. Overall our study shows that lack of PPARγ does not lead to defects in pancreatic beta cell function.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, KLF1 was strongly upregulated in IBxDU pigs (25.61), which suggest an important role of this TRF. Other important TRFs identified in the performed analysis were FOS and FOXO1 , involved in muscle differentiation and metabolism [63], but also in the regulation of adipogenic genes (as PPARG ) expression and IMF accumulation [54, 62]. These TRFs were also previously identified in BF muscle of newborn piglets [30].…”
Section: Discussionmentioning
confidence: 85%
“…FOXO1 is a member of the forkhead family of TRF, which exerts important regulatory functions in developmental processes including muscle development [ 103 , 104 ]. FOXO1 regulates expression of several adipogenic genes, including PPARG [ 105 ] and muscle cells differentiation in association with SMAD [ 106 ], although inconsistent information exits regarding its specific role [ 106 , 107 ]. Moreover, several TRF with known functions on adipogenesis and lipid metabolism were identified in the present regulators analysis ( CEBPA , CEBPG , ZFP423 , EGR1 , ATF2 , ATF4 and PPARGC1B) .…”
Section: Resultsmentioning
confidence: 99%